2013
DOI: 10.3842/sigma.2013.042
|View full text |Cite
|
Sign up to set email alerts
|

Fourier, Gegenbauer and Jacobi Expansions for a Power-Law Fundamental Solution of the Polyharmonic Equation and Polyspherical Addition Theorems

Abstract: Abstract. We develop complex Jacobi, Gegenbauer and Chebyshev polynomial expansions for the kernels associated with power-law fundamental solutions of the polyharmonic equation on d-dimensional Euclidean space. From these series representations we derive Fourier expansions in certain rotationally-invariant coordinate systems and Gegenbauer polynomial expansions in Vilenkin's polyspherical coordinates. We compare both of these expansions to generate addition theorems for the azimuthal Fourier coefficients.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Formula (8.9) can also be obtained as the special case ν = −n of formula (3.1) in Cohl [5]. In that formula he gives an explicit expansion of (z − x) −ν in terms of Jacobi polynomials P (α,β) n (x), where the expansion coefficients turn out to be constant multiples of the expressions (z − 1) α+1−ν (z + 1) β+1−ν Q (α+1−ν,β+1−ν) n+ν−1 (z) (the Q-functions being Jacobi functions of the second kind).…”
mentioning
confidence: 99%
“…Formula (8.9) can also be obtained as the special case ν = −n of formula (3.1) in Cohl [5]. In that formula he gives an explicit expansion of (z − x) −ν in terms of Jacobi polynomials P (α,β) n (x), where the expansion coefficients turn out to be constant multiples of the expressions (z − 1) α+1−ν (z + 1) β+1−ν Q (α+1−ν,β+1−ν) n+ν−1 (z) (the Q-functions being Jacobi functions of the second kind).…”
mentioning
confidence: 99%
“…For fixed z, this series converges uniformly in x ∈ [−1, 1] (see, e.g., [26, Chapter IX, Theorem 9.1.1]) and as shown in [5], it is valid for a set of parameters λ, γ, β containing R * + ×(−1, ∞) 2 . However, we shall restrict ourselves to the latter which is sufficient for our purposes and subsequent computations.…”
Section: Generalized Stieltjes Transform Of Beta Distributionsmentioning
confidence: 99%
“…Recently, this task was achieved in [5] for the family of Jacobi polynomials whence the generalized Stieltjes transform of any beta distribution in [−1, 1] follows after a simple integration. Using linear and quadratic transformations of the Gauss hypergeometric function, we retrieve the few examples of (1.1) given in [6] and prove for two larger classes of beta distributions that their generalized Stieltjes transforms are elementary functions (powers and fractions) of the Stieltjes transform of the Wigner distribution.…”
Section: Remindermentioning
confidence: 99%
“…We have since demonstrated that this technique is valid for a larger class of hypergeometric orthogonal polynomials. For instance, in [2], we applied this same technique to the Jacobi polynomials and in [5], we extended this technique to many generating functions for the Jacobi, Gegenbauer, Laguerre, and Wilson polynomials.…”
Section: Introductionmentioning
confidence: 99%